HUBUNGAN KARAKTERISTIK RESPONDEN DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN TERHADAP PROTOKOL KESEHATAN PENCEGAHAN COVID-19 DI KECAMATAN DATUK LIMA PULUH KABUPATEN BATU BARA - Beni Satria; Felix Kasim; Kuat Sitepu; Harris Rambey; Marice Simarmata; Sri Melda Br Bangun; Henri Gudmen Rionald Sihite (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
COVID-19iisianiinfectiousidiseaseicaused by SARS-CoV-2, cases are increasing and spreading rapidly throughout Indonesia. Batu Bara Regency is one of the districts that has experienced an increase in confirmed cases of COVID-19. The success ofitheiCOVID-19ihealth protocol is largely determined by the compliance of the community in carrying out the 3M movement, namely using masks, washing hands with soap, and maintaining physical distance. The purpose of this study was to determine the relationship between respondent characteristics and family support with compliance with the COVID-19 prevention health protocol in Datuk Lima Puluh District, Batu Bara Regency. This study was an observational analytic study with a cross sectional design. The population in this study were all people in Datuk Lima Puluh Subdistrict, Batu Bara Regency, amounting to 23,717 people and a total sample of 393 people. Data collection was carried out by interview guided by a questionnaire. Data analysis was performed by univariate and bivariate with the chi-square test. The results of the chi-square test show that there is a relationship between education and family support and adherence to the COVID-19 preventive health protocol. It is hoped that the health office and puskesmas can improve health socialization related to the prevention of COVID-19 so that people can comply with health protocols.